An Overview of Computational Fluid Dynamics Preoperative Analysis of the Nasal Airway - Xavier, Rui; Menger, Dirk-Jan; de Carvalho, Henrique Cyrne; Spratley, Jorge (Facial Plastic Surgery, 2021)
Evaluation of the nasal airway is crucial for every patient with symptoms of nasal obstruction as well as for every patient with other nasal symptoms. This assessment of the nasal airway comprises clinical examination together with imaging studies, with the correlation between findings of this evaluation and symptoms reported by the patient being based on the experience of the surgeon. Measuring nasal airway resistance or nasal airflow can provide additional data regarding the nasal airway, but the benefit of these objective measurements is limited due to their lack of correlation with patient-reported evaluation of nasal breathing. Computational fluid dynamics (CFD) has emerged as a valuable tool to assess the nasal airway, as it provides objective measurements that correlate with patient-reported evaluation of nasal breathing. CFD is able to evaluate nasal airflow and measure variables such as heat transfer or nasal wall shear stress, which seem to reflect the activity of the nasal trigeminal sensitive endings that provide sensation of nasal breathing. Furthermore, CFD has the unique capacity of making airway analysis of virtual surgery, predicting airflow changes after trial virtual modifications of the nasal airway. Thereby, CFD can assist the surgeon in deciding surgery and selecting the surgical techniques that better address the features of each specific nose. CFD has thus become a trend in nasal airflow assessment, providing reliable results that have been validated for analyzing airflow in the human nasal cavity. All these features make CFD analysis a mainstay in the armamentarium of the nasal surgeon. CFD analysis may become the gold standard for preoperative assessment of the nasal airway.
Keywords: computational fluids dynamics; nasal airflow; nasal airway; virtual surgery